Harnessing CCR2+ nonclassical monocytes to combat cancer metastasis - Bharat, Ankit (Henry Stewart Talks, 2025)
Nonclassical monocytes, Cancer metastasis, Natural killer cells, Immunotherapy-resistant cancers